Factors impacting organic corn production in the U.S. - Blue, Benjamin (Kansas State University, 2017)
The organic food industry experienced rapid growth over the past several decades. Typically, the majority of this growth is associated with the produce sector, but as consumers demand organic options for more food products, organic grains, dairy, and animal meat have emerged as viable food alternatives. There is currently a shortage of organic grains, specifically corn, to feed the livestock that provide organic meat and dairy products. This shortage has led to increased imports of organic corn in order to satisfy the domestic demand. Previous research comparing organic corn prices and profitability to conventional corn have shown organic corn production to be at least as profitable as conventional. With the declining value of cash receipts for conventional corn and the potential profitability advantage of organic corn, very few farmers are devoting acreage to organic corn in the U.S. This study seeks to determine potential economic reasons for this discrepancy. This research develops numerous production scenarios for organic corn in order to observe potential break-even yields a farmer could experience. For example, a nine-year low for price per bushel of organic corn was substituted in to actual values for current production to represent a possible break-even yield that could occur. In this study, the elasticity of organic corn is also calculated. The price elasticity of demand for organic corn gives insight as to how sensitive the demand is to a change in price per bushel. The findings in this study are expected to add insight to the reasons why U.S. farm production of organic corn is less than its domestic demand. It is hoped that famers will benefit from the results in this research in order to better understand organic corn production.
Keywords: Organic; Conventional; Corn Production; Break-Even Yield; Quantity Demanded